Effect of cold plasma on the quality parameters of custard apple juice milk beverage - K M, Shifa Sanofer Khair; G, Sujatha; Narayanan, Rita (Indian Journal of Dairy Science, 2023)
This study is aimed to investigate and compare the physicochemical quality parameters pH, acidity, and sensory qualities that are attributed to the freshness of the developed Custard apple juice milk beverage (CAJMB) subjected to cold plasma (CP) technology. The developed beverage was subjected to CP generated from two different configurations of Dielectric Barrier Discharge plasma (DBD) viz., High Voltage Atmospheric Cold Barrier Discharge plasma system (HV ACBD plasma system) and HV CBD Plasma torch/ Gun using Argon gas. The treatments were performed in different processing times (2 & 3 min) at an applied voltage gradient of 35 kV and 30 kV respectively. The treatments did not have any potential change in the sensorial quality attributes evaluated viz., colour, mouthfeel and flavour immediately after processing compared to untreated control sample. Though there was a noteworthy difference observed in pH and acidity after processing, directly proportional to increase in treatment conditions concerning voltage and processing time, the level of pH and acidity at defined intervals during storage showed a slow deterioration compared to the control during the storage period. In the control sample levels of pH and acidity breached the acceptable range in 3 to 5 days of storage, due to the formation of lactic acid by subsequent microbial growth. Whereas, CP treated sample using HV ACBD plasma system at 35kV for 3min exhibited promising results among other treatments and remained stable at refrigerated condition, with pH and acidity levels within the expected acceptable range for 9 to 10 days of storage.